Al-Manhaj Al-Qur’ānī Fī Mu’ālajaħ Zāhiraħ Mā Ba’da Al-Haqīqaħ : المنهج القرآني في معالجة ظاهرة ما بعد الحقيقة - Akbar, Rangga Satria; Saket, Saeed Abdullah Saeed; Rabbani, Muhammad Aqil (Civilization Research: Journal of Islamic Studies, 2023)
This research proved that post-truth has basic characteristics in this era, including: the spread of Hoax easily, the death of experience, and the presence of irritability of the people, and proved that the reason for all this is ignorance of the people, especially in their interest in reading and searching for the truth with a lack of awareness of that, and another reason is the lack of focus by the government in the face of the phenomenon of post-truth. This research revealed Quranic solutions to the issue, first, social monitoring by the government and the people to reduce the seriousness of the post-truth effect, Second, developing the educational quality in the hearts of the people to distinguish between right and wrong and be able to control the speed of emotion when searching for the truth and not forget the objective truth, so that the phenomenon of post-truth is what indicates the circumstances in which objective facts have less impact on public opinion compared to the influence of tendencies, emotions and personal beliefs.